High efficiency upcycling of post-consumer acrylonitrile-butadiene-styrene via plasma-assisted mechanochemistry - Nam, Yeonseo; Lee, Sangwoon; Jee, Sung Min; Bang, Joona; Kim, Jae Hong; Park, Jong Hyuk (Elsevier BV, 2024)
Recycling plastic waste has become of utmost importance due to the escalating volume of waste from electrical and electronic equipment (WEEE). Acrylonitrile-butadiene-styrene (ABS), with its superior impact strength and many applications, constitutes a significant portion of WEEE. Although diverse approaches to recycling ABS have been developed, there remains an unmet need to enhance the mechanical properties of post-consumer recycled ABS with high recycling efficiency. The major hurdle to recycling ABS is caused by the thermo-oxidative degradation of the butadiene phase and phase separation between ABS and additives, which reduce the impact strength. Conventional methods employed compatibilizers and organic solvents to improve the compatibility between ABS and additives. Nevertheless, these approaches typically consume large amount of solvents, and thereby have limitations in terms of process feasibility, recycling efficiency, and environmental considerations. Here, we used plasma-assisted mechanochemistry (PMC) to upcycle post-consumer ABS through blending it with styrene-butadiene-styrene (SBS) to enhance its mechanical properties. By concurrently applying high-energy mechanical forces and plasma gases in a dry condition, PMC induced chemical bond between oxidatively degraded ABS and radical-formed SBS chain. The improved interfacial affinity led to an overall homogeneous distribution of SBS particles within the ABS matrix, resulting in a reduction in particle size. Therefore, the PMC-processed upcycled ABS blends could endure high external forces with enhanced impact strength and elongation at break. Consequently, our PMC-based approach demonstrates an upcycling process of post-consumer ABS with high recycling efficiency that is also eco-friendly.